The design and the implementation of the development strategy at public higher education institutions = Projektowanie i implementacja strategii rozwoju w publicznych szkołach wyższych - Wyrwa, Joanna (Zielona Góra: Faculty of Economics and Management Press)
This article focuses on identification of the model approach to designing and implementing a development strategy in a higher education institution. The main reason for taking up the topic of formulating and implementing development strategies in higher education institutions is the growing demand for developing a model of designing and implementing strategies in entities of this type.
Keywords: szkoła wyższa; strategia; Zarządzanie strategiczne; higher education institution; strategy; Strategic management